German multiple-product, multiple-destination exporters: Bernard-Redding-Schott under test - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2012)
Export is dominated by enterprises that trade more than one good with customers in more than one destination country. Germany, one of the leading actors on the world market for goods, is a case in point. Theoretical models of multiple-product, multipledestination exporters that can guide empirical research of their production and export decisions are still rare. Recently, Bernard, Redding and Schott (QJE 2011) published a general equilibrium model that serves this purpose and find support for many of its implications in U. S. trade data. This note uses newly available transaction-level data for German manufacturing firms for an empirical test of implications of this model. Results are strikingly similar to findings reported for the United States.
Keywords: F14; 330; multi-product exporters; multi-country exporters; Germany; Mehrproduktproduktion; Außenhandelsstruktur; Exportindustrie; Schätzung; Verarbeitendes Gewerbe; Deutschland